Efficacy of Diclofenac in Pain Reduction after Topography-Guided Transepithelial Surface Ablation - Jost, Moritz; Pfaeffli, Oliver; Kaufmann, Claude; Reichmuth, Valentina; Thiel, Michael; Baenninger, Philipp (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To report the efficacy of postoperative diclofenac eye drops for pain reduction in patients undergoing topography-guided transepithelial surface ablation.Methods Retrospective consecutive case series of patients undergoing topography-guided transepithelial surface ablation for refractive myopia treatment using a 1 KHz excimer laser. Patients were divided into three groups. Group 1 did not receive any diclofenac drops, group 2 received one diclofenac drop postoperatively (day 1), and group 3 received one drop of diclofenac postoperatively (day 1) and on the day after treatment (day 2). Postoperative pain was self-assessed by patients per eye daily for the first 4 consecutive days (days 1 to 4) after the treatment using the visual analogue scale (VAS). We compared VAS with respect to the use of additional oral or topical treatment as well as VAS with regards to the total amount of ablated tissue (< 50 µm, 50 – 100 µm, ≥ 100 µm) among the groups.Results We enrolled 163 eyes of 163 patients (55.0% female), with a mean age of 31.3 years (SD ± 6.6; range 21 – 68). We excluded 16 patients who applied other additional analgesics. Group 1 comprised 35 eyes (21%), group 2 had 21 eyes (13%), and group 3 consisted of 107 eyes (66%). Median pain score (VAS) was 5 (range 0, 10) in group 1, which was higher than in groups 2 (median 1, range 0 to 7) and 3 (median 1.5, range 0 to 7) on the day of surgery (p < 0.0001). Percentage of patients using an additional oral NSAID on days 1 and 2 was significantly higher in group 1 (69/83%) when compared to groups 2 (24/43%) or 3 (31/49%) (p < 0.001 day 1, p = 0.001 day 2). No correlation was found between pain sensation and maximum ablation depth (Spearman correlation p > 0.05).Conclusion The instillation of one drop of diclofenac after topography-guided transepithelial surface ablation reduced subjective pain sensation according to VAS and decreased the need for additional topical anesthetic drops or oral NSAID.
Keywords: pain reduction; surface ablation; efficacy